2017
DOI: 10.25077/adj.v5i2.79
|View full text |Cite
|
Sign up to set email alerts
|

PERBANDINGAN EFEKTIVITAS BUAH STROBERI (Fragaria x ananassa) DENGAN BUAH JERUK NIPIS (Citrus aurantifolia) SEBAGAI BAHAN ALAMI PEMUTIH GIGI SECARA IN VITRO

Abstract: One of the aesthetic problem which had bother and become a complaint was teeth discoloration that can be overcome by dental bleaching procedures. The use of tooth whitening ingredient can cause side effects such as tooth sensitivity and mucous irritation. Therefore, many researchers have been looking for a safer alternatives materials  to be used as tooth whitening ingredients including Strawberry (Fragaria x ananassa) contain of elegat acid and malic acid and Lime (Citrus aurantifolia) contain of citric acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Activated charcoal forms binding bonds and subsequently expels these substances from the mouth and body. Therefore, when activated charcoal is applied to the tooth surface, its exceptional absorption power helps absorb chromogen deposits and other factors within the enamel that alter tooth color [1,21] The significance of using toothpaste containing lime is highlighted in the results of another study conducted by Nurhaeni [22] which demonstrated that lime fruit at a concentration of 2.5% produced the most significant average difference in tooth color, specifically 6.20. Furthermore, research by Rochmah et al [23] indicates that lime (Citrus aurantifolia) has the potential to whiten discolored tooth enamel and identifies an optimal timeframe for achieving this effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated charcoal forms binding bonds and subsequently expels these substances from the mouth and body. Therefore, when activated charcoal is applied to the tooth surface, its exceptional absorption power helps absorb chromogen deposits and other factors within the enamel that alter tooth color [1,21] The significance of using toothpaste containing lime is highlighted in the results of another study conducted by Nurhaeni [22] which demonstrated that lime fruit at a concentration of 2.5% produced the most significant average difference in tooth color, specifically 6.20. Furthermore, research by Rochmah et al [23] indicates that lime (Citrus aurantifolia) has the potential to whiten discolored tooth enamel and identifies an optimal timeframe for achieving this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, brushing with activated charcoal leads to a change in tooth enamel color through direct contact with the tooth surface [20] . In a study conducted by Nurhaeni et al [22] , it was determined that strawberries (Fragaria x ananassa) with a concentration of 100% were more effective in whitening teeth compared to limes (Citrus aurantifolia) with a concentration of 2.5%. However, there was no significant difference in their whitening effects.…”
Section: Discussionmentioning
confidence: 99%
“…Malic acid can bind calcium and cause the occurrence of porosity of enamel crystals. This causes a break in the conjugate bonds with dye molecules and erodes the enamel layer so that it gives a whitening effect and makes the tooth color more neutral [24]. When measuring using a shade guide, lighter colors are indicated by lower scores.…”
Section: Discussionmentioning
confidence: 99%